Multicomponent Zn(1-x)Fe0.8xNa0.2xO semiconductors: Effect of dopant concentration and ionic radius on structural, opto-electronics, magnetic and sensing properties. (1st August 2019) - Bajpai, Gaurav; Ostawal, Mayank; Moirangthem, Igamcha; Bajpai, Shubhra; Basaula, Dharma R.; Khan, Mahmud; Liu, Shun-Wei; Biring, Sajal; Sen, Somaditya
Abstract: Fe incorporation in ZnO lattice draws more oxygen which reduces oxygen vacancies. The smaller size and larger charge of the Fe 3+ ion helps to reduce strain initially but with increased substitution generates more strain due to excess oxygen and structural deformation. The mismatch of ionic radii may be addressed by co-substituting with a larger element but with lesser charge. Oxygen defects play a vital role in magnetization and UV-sensing properties of pure ZnO. Oxygen vacancy mediated ferromagnetic exchange interaction should reduce in Fe-doped ZnO due to reduction oxygen vacancies. Similarly UV-sensing should also decrease. Larger sized Na + co-incorporation, with smaller Fe 3+, helps retention of oxygen vacancies in Zn(1- x ) Fe(0.8 x ) Na(0.2 x ) O ( 0 ≤ x ≤ 4/128 ) enhancing magnetization and enabling faster UV-sensing properties. The x = 4 ∕ 128 sample reveals promising magnetization and shows faster UV-sensing. Graphical abstract: Image 1